Moisture characteristics of warm mix asphalt containing reclaimed asphalt pavement (RAP) or steel slag - Goli, Hadi; Latifi, Manouchehr; Sadeghian, Mohammad (Materials and structures, 2022)
Issues like limitation of natural resources of aggregates, global warming, need for eco-friendly, cost-effective, and high performance and durable asphalt mixture, have made the Reclaimed Asphalt Pavements Warm Mix Asphalt (RAP-WMA) and Steel Slag Warm Mix Asphalt (SS-WMA) interesting substitutions for conventional Hot Mix Asphalt mixtures. Furthermore, presence of moisture initiates and accelerates the deterioration of both of these mixtures. In this way, the response of the RAP-WMA to the moisture damage was compared with the SS-WMA using experimental tests including Indirect Tensile fatigue failure, Resilient Modulus, Indirect Tensile Strength, Semi-circular Bending, and Dynamic Creep tests. The obtained results show that although the RAP-WMA and SS-WMA mixtures contain hydrophilic and moisture sensitive aggregates and aged binder, they had an appropriate performance against the effect of moisture. Also, the SS-WMA mixtures showed better performance against moisture than the RAP-WMA mixtures, and therefore, they can be recommended as a substitution for RAP-WMA in regions where moisture damage is prevailing.